计算:::(-3)^m+3(-3)^m-1的值是
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 04:39:41
计算:::(-3)^m+3(-3)^m-1的值是计算:::(-3)^m+3(-3)^m-1的值是计算:::(-3)^m+3(-3)^m-1的值是(-3)^m+3(-3)^m-1=(-3)^m-(-3)
计算:::(-3)^m+3(-3)^m-1的值是
计算:::(-3)^m+3(-3)^m-1的值是
计算:::(-3)^m+3(-3)^m-1的值是
(-3)^m+3(-3)^m-1
=(-3)^m-(-3)(-3)^m-1
=(-3)^m-(-3)^m
=0
(-3)^m+3(-3)^m-1
=(-3)(-3)^m-1+3(-3)^m-1
=0
额
-12m-1
计算:(m+3m+5m+...+2009m)-(2m+4m+6m+...+2008m)
计算:(m+3m+5m+...+2009m)-(2m+4m+6m+...+2010m)
计算(m^2-9)/[m(m-3)+m-3]
计算m(m+7)-(m+3)(m-2).
计算 -(X^3)^M
计算(m+3m+5m+7m+.+2009m)-(2m+4m+6m+.+2008m)
计算(m+3m+5m+7m+.+2013m)-(2m+4m+6m+.+2012m)
计算(m^3)^4+m^10m^2+m*m^3*m^8
计算:(2m*7m*3m)/(-42)m.(m为正整数)m是次方
计算:m-2m-3m+4m-5m-6m+7m-8m-9m+...+2002m-2003m-2004m
m(x+3m)²怎么计算
计算:(m+3)( )=m^2-9
计算27^m/9^m/3
27^m/9^m/3计算
计算(m+3m+5m……+2009m)—(2m+4m+6m+2008m)=
计算:(m+3m+5m+…+2015m)-(2m+4m+6m+…+2014m)=
计算(m+3m+5m+.+2009m)-(2m+4m+6m+.+2010m)=多少
计算(m+3m+5m+.+2011m)减(2m+4m+6m+.+2012m)=